2020
DOI: 10.1183/13993003.00217-2020
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study of DNA methylation and adult asthma in the Agricultural Lung Health Study

Abstract: Epigenome-wide studies of methylation in children support a role for epigenetic mechanisms in asthma. Studies in adults are rare, and few have examined non-atopic asthma. We conducted the largest epigenome-wide association study of blood DNA methylation in adults in relation to non-atopic and atopic asthma.We measured DNA methylation in blood using the Illumina MethylationEPIC array among 2286 participants in a case-control study of current adult asthma nested within a U.S. agricultural cohort. Atopy was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 58 publications
(67 reference statements)
0
43
0
Order By: Relevance
“…IgE sensitization to food and airborne allergens usually starts during early childhood and is for many children the first step in the progression to clinical manifestations such as atopic eczema, food allergy, seasonal or perennial rhinitis, and/or asthma [ 4 ]. In recent years, some studies have evaluated the association between DNA methylation and the development of allergen-specific IgE sensitization [ 5 , 6 , 7 , 8 , 9 ]. However, the cross-sectional design of these studies imposes the limitation that it is not possible to know if the observed DNA methylation differences are a consequence of the ongoing atopic reactions or precede the inception of immunoglobulin E (IgE) sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…IgE sensitization to food and airborne allergens usually starts during early childhood and is for many children the first step in the progression to clinical manifestations such as atopic eczema, food allergy, seasonal or perennial rhinitis, and/or asthma [ 4 ]. In recent years, some studies have evaluated the association between DNA methylation and the development of allergen-specific IgE sensitization [ 5 , 6 , 7 , 8 , 9 ]. However, the cross-sectional design of these studies imposes the limitation that it is not possible to know if the observed DNA methylation differences are a consequence of the ongoing atopic reactions or precede the inception of immunoglobulin E (IgE) sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…An Epigenome-Wide Association Study found that STX6 may one of genes that associated with atopic asthma. They also reported that STX6 may has a role in methylate process that is seen in this disease (28) In other studies, the association between PLCB1 and the decrease of FEV1 and FEV1/FVC in their participation was shown (29). Another study reported that PLCB1 at least in two pedigree with severe COPD was observed (30) Other group found an association between ZNF33A gen and remission from asthma(31) LARP4B is a target gene of miR106 inhibition of miR-106b that suppressed the mRNA and protein expression of cancer-related genes (32).…”
Section: Discussionmentioning
confidence: 86%
“…Consequently, CLC was included in transcriptomic cluster TAC1 of patients with high sputum eosinophilia in the abovementioned U-BIOPRED asthma study 37 and associated with asthma in an epigenome-wide association study (EWAS) 44 .…”
Section: Charcot-leyden Crystal Protein (Clc)mentioning
confidence: 99%
“…Since IL13-stimulated parkin aids mono-ubiquitination of EPS15 thus preventing RTKs internalization and potentializing the effects of TGF-b, it forms a link between the two pro-brotic cytokines as well as mtDNA-mediated in ammation. EPS15L1, a protein of suggested role in the process of receptor endocytosis, coimmunoprecipitates with EPS15 and is one of the genes associated with asthma in an EWAS study 44 and EPS15 transcript is upregulated in human ASM cells upon their stimulation 87 .…”
Section: Deiodinase Iodothyronine Type III (Dio3)mentioning
confidence: 99%